LEGAL ASPECTS OF BANKRUPTCY PEACE THROUGH RESTRUCTURING CORPORATE DEBT IN THE DIGITAL ECONOMY ERA - Ida Nadirah (CV. RADJA PUBLIKA, 2025)
This type of research is analytical descriptive, which aims to describe legal phenomena related to bankruptcy peace and debt restructuring in the digital economy era, then analyze them based on legal theory and practice in the field. Bankruptcy is regulated in Law no. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU). In this framework, peace is one solution to avoid total liquidation of company assets, with a focus on debt restructuring and paying off obligations to creditors. Based on a literature review, peace is considered more effective than liquidation because it gives the company the opportunity to recover and continue operating. The legal aspects of bankruptcy peace through debt restructuring are very relevant in the digital economy era. However, to answer the new challenges faced by companies and creditors, Indonesia needs a legal framework that is more adaptive, dynamic and responsive to technological developments. A collaborative approach between regulators, business players and other stakeholders is the key to creating a legal ecosystem that supports the sustainability of the digital economy.